2016
DOI: 10.1007/s00411-016-0658-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of gamma H2AX foci in healthy volunteers and health workers occupationally exposed to X-irradiation and its relevance in biological dosimetry

Abstract: Gamma-H2AX (γ-H2AX) assay is a marker to measure double-strand breaks in the deoxyribonucleic acid. Variables such as age, oxidative stress, temperature, genetic factors and inter-individual variation have been reported to influence the baseline γ-H2AX focus levels. Therefore, knowledge on baseline frequency of γ-H2AX foci in a targeted population would facilitate reliable radiation triage and dose estimation. The objective of the present study was to establish the baseline data using blood samples from health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Lastly, the frequency of γ-H2AX foci, a marker of DNA double-strand breaks, was found to be significantly higher in IR-exposed workers compared to healthy volunteers [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the frequency of γ-H2AX foci, a marker of DNA double-strand breaks, was found to be significantly higher in IR-exposed workers compared to healthy volunteers [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the comet assay, γ-H2AX level can be measured in cells directly after exposure, without the need for lengthy culture. Raavi et al showed that this method might also find some use in occupational exposure estimation [71]. The authors observed a significantly increased number of γ-H2AX foci in lymphocytes from occupationally exposed health workers (exposed to X-rays) compared to matched controls.…”
Section: Other Candidate Methods For Biological Dosimetrymentioning
confidence: 99%
“…The biodosimetry laboratory of the Human Genetics department of our institution has already established the gold standard DC assay to verify the excess radiation exposures registered in occupational workers within the country and provided the service as per the regulatory agency requirement. In parallel, the lab developed an alternative to chromosome-based assays [Bhavani et al, 2014;Meenakshi et al, 2021; and cell-based assays [Raavi et al, 2016;Venkateswarlu et al, 2015] and participated in inter-laboratory comparison exercises organized by RENEB network [Gregoire et al, 2021].…”
Section: Discussionmentioning
confidence: 99%